Lifestyle and Sales Promotion in Impulsive Purchases of Hijab by Students of the Department of Administrative Sciences, Faculty of Social Sciences and Law, Universitas Negeri Makassar - Triana Putri Herianto, Triana Putri Herianto; Muh. Nur Yamin; Andi Muhammad Rivai; Sirajuddin Saleh; Aris Baharuddin (Business Research and Administration Innovation, 2025)
Lifestyle and Sales Promotion on Impulsive Hijab Purchases in Administrative Sciences Students, Faculty of Social Sciences and Law, Makassar State University. Thesis, Business Administration Study Program. Administration Science Department. Faculty of Social Sciences and Law. Makassar public university. This study aims to determine the effect of lifestyle and sales promotion on impulsive hijab purchases among female students of the Administrative Sciences Department, Faculty of Social Sciences and Law, Makassar State University. This research is a type of descriptive quantitative research approach. Data collection techniques used in this study are questionnaires or questionnaires and documentation. The sample in this study were female students of the Administrative Sciences Department, Faculty of Social Sciences and Law, Makassar State University, Class of 2018-2020. The data were obtained from research results that were processed using the SPSS version 25 software program which consisted of validity tests, reliability tests, descriptive analysis, Multiple Linear Regression Analysis, Hypothesis Tests, and Coefficients of Determination. The results of the study show that the variables Lifestyle and Sales Promotion simultaneously influence Impulsive Hijab Purchases with an Fcount of 25.094 > Ftable of 3.10 with a significance level of 0.000 (sig ἀ <0.05). Based on test the coefficient of determination of the relationship between Lifestyle and Sales Promotion together on Impulsive Buying is quite significant for Students of the Department of Administrative Sciences, Faculty of Social Sciences and Law, State University of Makassar.